Towards a Systemic Assessment of Gendered Energy Transition in Urban Households - Josephine Kaviti Musango (MDPI AG, 2021)
Assessment of gendered energy transition at an urban scale has emerged as a challenging issue for researchers, policy makers and practitioners. With municipalities becoming players in the energy markets, their involvement raises policy issues that need to be better assessed in supporting gendered energy transition. This paper, therefore, contributes to gendered energy transition assessments at urban household level from a policy maker perspective. We developed a system dynamics model to assess the effects of urban energy policy interventions on household energy consumption and gendered measures using Drakenstein Municipality as a case study. The study used secondary data from various sources for the model parameters. We tested three hypothetical policy scenarios: the business-as-usual, the energy subsidy policy and the energy efficiency policy. The results show that understanding the changes in urban household energy consumption and gendered measures due to energy transition interventions is essential for urban policy planning. The energy subsidy policy scenario was observed to increase total energy consumption but also resulted in socio-environmental impacts that might increase inequality and impair human health. Urban household energy transition interventions need to consider a systems approach to develop decision support tools that capture the cross-sector impacts and inform the development of interventions that promote gendered household energy transition.